AMERICAN LITERARY STUDIES IN UKRAINE: ACADEMIC DISCIPLINE OR A MOVER TOWARDS SOCIAL CHANGES? - VYSOTSKA, Natalia (Studia Universitatis Babeș-Bolyai Philologia, 2017)
American Literary Studies in Ukraine: Academic Discipline or a Mover towards Social Changes? The paper presents an overview of the past and the present of American literary studies in Ukraine since the nation’s independence in 1990. We argue that American diverse experiences in finding the workable balance between an individual and the state as recorded in literature and shaped by it have been of special significance for Ukraine as potential models in its quest for new national identity. The paper discusses institutional forms of teaching and studying American Literature, recent publications in the field, as well as current theoretical trends in Ukrainian scholars’ approaches to the works authored by US writers. REZUMAT. Studii literare americane în Ucraina: disciplină academică sau îndemn spre schimbări sociale? Lucrarea de față trece în revistă evoluția istorică a studiilor literare americane în Ucraina, de la câștigarea independenței naționale în 1990 și până în prezent. Susținem că varietatea de experiențe americane în ce privește atingerea unui echilibru funcțional între individ și stat, așa cum se regăsesc în literatură, au o semnificație deosebită pentru Ucraina, în sensul că oferă modele ce pot ghida în demersul formării unei noi identități naționale. Lucrarea discută forme instituționalizate de predare și studiere a literaturii americane, publicații recente în domeniu, precum și tendințele teoretice actuale, așa cum se reflectă ele în modul de abordare a operei scriitorilor americani de către specialiști ucrainieni. Cuvinte cheie: studii literare americane, Ucraina, identitate națională, schimbări sociale, postmodernism, milticulturalism.